An innovative hybrid optimization approach for sustainable milling of support structures in additively manufactured Ti-6Al-4V components utilizing NSGA-III and COBRA - Akcadirci, Ahmet; Yapan, Yusuf Furkan; Altan, Mihrigul Eksi; Khan, Aqib Mashood; Uysal, Alper (SPRINGER LONDON LTD, 2025)
Problems such as bending, collapsing, and therefore inability to cut occur in the cleaning of support structures used in additive manufacturing. For this reason, cleaning supports increases both costs and production time, as well as sustainability concerns due to the increasing work volume in the world of metal additive manufacturing. In addition, cleaning of support structures is usually performed manually by the operator, and since this situation can not provide the expected mechanical properties, precise surface, and dimensional tolerances from the part, the operator's effectiveness in the process must be reduced. For these reasons, there is a need to clean support structures successfully and sustainably. This study investigated the sustainable milling of additively manufactured as-built and annealed support structures from Ti-6Al-4V alloy using different feed values under dry, minimum quantity lubrication (MQL) with vegetable-based cutting oil and MQL with graphene nanoparticle-reinforced nanofluid (N-MQL) cutting conditions in terms of cutting force, energy consumption, and circumferential and areal damage. After that, a novel hybrid optimization was performed by combining the Non-dominated Sorting Genetic Algorithm III (NSGA-III) multi-objective optimization method and the Comprehensive Distance Based Ranking (COBRA) multi-criteria decision-making method. The N-MQL method improved the cutting force, energy consumption, circumferential damage, and areal damage by 15.2%, 0.086%, 18.4%, and 16.8%, respectively, compared to the dry cutting condition. It has been determined by the novel hybrid optimization that milling the as-built Ti-6Al-4V alloy support structure under the N-MQL cutting condition at a feed value of 0.05-0.0554 mm/rev is optimum in terms of both machining performance and sustainability. It has been concluded that cutting the support structures from the additively manufactured components before the annealing process is more appropriate, rather than annealing them simultaneously with the primary portion, then cutting.
Keywords: Ti-6Al-4V; Support structure; Minimum quantity lubrication; Graphene nanofluid, NSGA-III; COBRA; MECHANICAL-PROPERTIES; FINISH; MACHINABILITY; BEHAVIOR; MQL; Automation & Control Systems; Engineering